2016
DOI: 10.1186/s40508-016-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of modern plant breeding and enzyme technology to obtain highly enriched erucic acid from Crambe oil

Abstract: Background: Fatty acids from vegetable oils are useful building blocks for industrial materials. The purpose of this work was to prepare erucic acid with high purity from a vegetable oil. High purity erucic acid is used for the production of erucamide with applications in plastics manufacturing. A newly developed transgenic Crambe line produces seed oil with 68 % erucic acid compared to 53 % in the wild type oil.Results: Further enrichment of erucic acid from Crambe (wild type and transgenic) oil was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For instance, C22:1 in Crambe oil is mostly located at the sn ‐1,3 positions of the glycerol and the remaining FA in this oil are prone to be located at the sn ‐2 position . Interestingly, although some studies showed that C22:1 enrichment could be achieved utilizing sn ‐1,3 specific lipases, this strategy was less successful than using lipases with natural selectivity towards long‐chain fatty acids like C. rugosa or G. candidum lipase ,. In order to analyze the enrichment capacity of the newly created CAL‐A variants depending exclusively on the different chain length of the FA present in the oils, FA ethyl ester (EE) derivatives obtained from Crambe and Camelina oils were used as substrates.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, C22:1 in Crambe oil is mostly located at the sn ‐1,3 positions of the glycerol and the remaining FA in this oil are prone to be located at the sn ‐2 position . Interestingly, although some studies showed that C22:1 enrichment could be achieved utilizing sn ‐1,3 specific lipases, this strategy was less successful than using lipases with natural selectivity towards long‐chain fatty acids like C. rugosa or G. candidum lipase ,. In order to analyze the enrichment capacity of the newly created CAL‐A variants depending exclusively on the different chain length of the FA present in the oils, FA ethyl ester (EE) derivatives obtained from Crambe and Camelina oils were used as substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Two well-established oilseed crops are soybean (Glycine max L.) and canola (Brassica napus), producing over 400 million metric tons of seed, annually, rich in both oil and protein (USDA, United States Department of Agriculture Foreign Agriculture Services, 2013). The oils from these crops can be used in a plethora of products including foodstuffs, feed, cosmetics, and industrial lubricants along with biodiesel and biojet fuels (Dyer et al, 2008;Volkova et al, 2016). However, it is important to balance needs for human nutrition with those of bio-based products.…”
Section: Introductionmentioning
confidence: 99%
“…Pennycress can yield up to 840 liters of oil per hectare, with a potential of United States Midwest Corn Belt-grown pennycress to replace ∼5% of petroleum sources currently used in the United States (Moser et al, 2009;Boateng et al, 2010;Fan et al, 2013;Mousavi-Avval and Shah, 2020). In addition to possible uses for biofuels, food, and feed production, the seed oil-derived fatty acids (FAs) can be processed to produce wax esters which are used in cosmetics, surfactants, lubricants, and plastics (Volkova et al, 2016). A main objective of research on pennycress is altering its seed lipid profile to create value-added feedstocks better suited for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…6,[27][28][29] The oil from seeds is used for production of plastic lms, adhesives, nylon, thermal insulation, corrosion inhibitors, synthetic rubber and industrial lubricant. [30][31][32][33] It can also be used for biodiesel production 34 due to its high resistance to degradation and oxidation. 35 Rened Crambe oil can be used for cosmetics and waxes production.…”
Section: Crambe Plants: Agronomic Features and Seed Oil Contentmentioning
confidence: 99%